Women Workers and Professional Zakat Literations - Sri Abidah Suryaningsih (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
Zakat of Profession is for the career men and career women, that Islam doesn’t differentiate the rule of mahdhah worship (the terms and commandment are already set). The women also have the responsibility to do all the duties which are stated in Islam. The purpose of this article is to analyze the understanding of the literation of profession zakat for career women. This article uses a descriptive qualitative analysis method. The result describes that the respondents understand the terms of zakat which is equated with the general terms of zakat, while there are still many opinions the pro and contra about the obligation of taking out the zakat of the profession, According to the informants, the time to distribute the zakat of a profession is once a month as they get the salary, while other said once a year. The informants understand the terms of zakat of a profession as the one who is obligated to give the zakat, and some informants understand about the percentage of their salary as the zakat of the profession, while some of them do not understand yet about the number of zakat of the profession.